(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2025)
ABSTRACT This article describes the main causes of difficulty in communicating fluently in English, development methods, and explores methods that can be used in different learning environments. The study analyzes the existing literature, the practical methods used by countries with advanced English speaking skills, and based on them, a number of suggestions for the development of communication skills are presented. Also, the article provides information about the importance of developing speaking skills in English, which is now among the world’s most recognized languages.